Teorías implícitas y explícitas en los procesos de enseñanza y aprendizaje del solfeo. (2014)
This study explores the characteristics of similarity and divergence between the pedagogical discourse of teachers and their performance in the classroom, from the different educational paradigms that guide, today, the educational events. The teaching and learning of music theory constitute the backbone of the proposed curriculum of the Department of Music, which has implications in the other musical areas and, therefore, the training program that orients the area of music theory, requires an assessment of the impacts and effects caused by the performance of the teacher in charge of running this course as an essential condition to establish elements of building and transfer of knowledge in each of the disciplines that make up the curricular structure of the Department of Music.